Faktor-Faktor Yang Berhubungan Dengan Perilaku Wanita Usia Subur Terhadap Deteksi Dini Ca Mammae Menggunakan Teknik Sadari - Lia Artikasari; Herinawati Herinawati; Enny Susilawati (JURNAL ILMIAH OBSGIN : Jurnal Ilmiah Ilmu Kebidanan & Kandungan P-ISSN : 1979-3340 e-ISSN : 2685-7987, 2021)
Cancer is a condition of abnormality in the body's organ tissues in the form of the growth of abnormal cells rapidly, and ultimately interfere with the performance of normal cells. The trend of cancer continues to increase from year to year, especially in developing countries. This study aims to analyze the factors related to the behavior of women of childbearing age towards the Early Detection of Ca Mammae using the Sadari technique at Paal V Public Health Center Jambi City. This type of research is observational analytic using a cross sectional design. This research was conducted in July-August 2018 involving 98 WUS who visited the Paal V Health Center. The dependent variable in the study was the behavior of women of childbearing age towards Early Detection of Ca Mammae while the independent variables were knowledge, motivation and sources of information. Data analysis using chi square with a significance level of 95%. The results showed that there was a significant relationship between knowledge (0.043), motivation (0.017), and sources of information (0.000).